Developing the Speaking Fluency of Tenth-Grade Students Through Cartoon Films at SMAN 1 Bulagi Selatan, Banggai Kepulauan - Asmiranda Rajak; Mawardin M Said; Moh Abraham A Eisenring; Mochtar Marhum (Journal of General Education and Humanities, 2026)
Students at SMAN 1 Bulagi Selatan experienced difficulties in speaking English fluently due to limited vocabulary, lack of confidence, and insufficient opportunities to practice speaking. This research aims to examine whether the use of cartoon films can improve students’ English speaking fluency. The research employed a pre-experimental design using a one-group pretest and posttest approach. The sample consisted of 19 tenth-grade students of SMA Negeri 1 Bulagi Selatan. Data were collected through speaking tests administered before and after the treatment. The treatment involved the use of cartoon films in interactive speaking activities such as discussions, role plays, and storytelling. The results showed a significant improvement in students’ speaking fluency, as indicated by the increase in the mean score from 40.79 in the pretest to 69.74 in the posttest. Statistical analysis using the Wilcoxon Signed Ranks Test revealed a significance value of 0.000, indicating a statistically significant difference between the pretest and posttest scores. These findings suggest that cartoon films can be used as an instructional medium to improve students’ speaking fluency. The use of cartoon films may also support students’ confidence and participation during speaking activities.